(untitled) (Journal of the College of Basic Education, 2026)
The study aimed to assess the level of creative thinking among students prior to the implementation of the educational intervention. It also sought to evaluate the effectiveness of the project-based learning strategy in teaching art education, as well as the efficiency of the cooperative learning strategy in the same context. Additionally, the study aimed to determine the extent of the impact resulting from the application of each strategy on a sample of students, with a particular focus on the influence of project-based learning in developing creative thinking. To achieve these objectives, the researcher adopted a quasi-experimental approach using two experimental groups. The first group was taught using the project-based learning strategy, while the second group was taught through cooperative learning. The impact of each strategy on creative thinking skills—such as fluency—was measured. The findings revealed that project-based learning had a significant effect on enhancing creative thinking among art education students, with a noticeable and high difference between the pre-test and post-test results on the creative thinking scale. Based on these results, the study recommended that faculty members in art education departments should be encouraged to offer enrichment and guidance programs that support the development of creative thinking among students. As an extension of the current research, the researcher proposed further investigation into the effect of project-based learning on developing students’ skills in sculpture within the art education department.